Produção e beneficiamento de sementes de trigo na empresa Sementes Estrela Erechim,RS - Webber, Tiago Antonio (2009)
The objective of the present study was to analyze the efficiency of wheat seed production and conditioning at the Sementes Estrela seed company located in the Erechim county, RS state, Brazil, during 2006/07, 2007/08 and 2008/09 crop seasons. Data of area and volume registered for seed production, receiving, conditioning and aprovation, germination and comercialization of wheat seed lots. Cultivars studied were: Abalone; Safira; Alcover; Pampeano; Onix; Quartzo; Marfim; BRS Timbauva; BRS Guamirim; BRS 208; Fundacep Nova Era; Fundacep 52; Fundacep Cristalino e Fundacep Raizes. The results shown that wheat seed production at Sementes Estrela represents 3.87% of the state of Rio Grande do Sul production. There is a difference between registered volume and volume received of wheat seeds of about 15%. The efficiency of wheat seed conditioning is increasing each crop season, being the seed loss of about 22%. In the last two crop seasons the wheat seed conditioned and approved is 100%. Germination of approved seed lots is above the standard stablished by the seed company in all crop seasons. Commercialization of wheat seeds at Sementes Estrela company is above 90% of seed lots conditioned but shows a tendency of reducing in the last crop season.